Sirtuins: Molecular Traffic Lights in the Crossroad of Oxidative Stress, Chromatin Remodeling, and Transcription - Rajendran, Ramkumar (Hindawi Publishing Corporation, 2011)
Transcription is regulated by acetylation/deacetylation reactions of histone and nonhistone proteins mediated by enzymes called KATs and HDACs, respectively. As a major mechanism of transcriptional regulation, protein acetylation is a key controller of physiological processes such as cell cycle, DNA damage response, metabolism, apoptosis, and autophagy. The deacetylase activity of class III histone deacetylases or sirtuins depends on the presence of NAD(+) (nicotinamide adenine dinucleotide), and therefore, their function is closely linked to cellular energy consumption. This activity of sirtuins connects the modulation of chromatin dynamics and transcriptional regulation under oxidative stress to cellular lifespan, glucose homeostasis, inflammation, and multiple aging-related diseases including cancer. Here we provide an overview of the recent developments in relation to the diverse biological activities associated with sirtuin enzymes and stress responsive transcription factors, DNA damage, and oxidative stress and relate the involvement of sirtuins in the regulation of these processes to oncogenesis. Since the majority of the molecular mechanisms implicated in these pathways have been described for Sirt1, this sirtuin family member is more extensively presented in this paper.